Analisis Efisiensi Distribusi Material Konstruksi Menggunakan Pendekatan Supply Chain Management pada PT Waskita Karya (Persero) Tbk - Risda Marvinita; Tiara Prisaca Sabilla; Muhammad Ramadhani Sanjaya (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the efficiency of construction material distribution using a Supply Chain Management (SCM) approach at PT Waskita Karya (Persero) Tbk. The research employed a descriptive qualitative approach with a case study method. The data used were secondary data collected through documentation studies and literature reviews from news articles, company reports, scientific journals, and relevant literature. The study focused on the issue of material distribution delays in the 500 kV electricity transmission project in Sumatra, which affected project completion. The findings indicate that delays in material delivery were caused by suboptimal supply chain management, particularly in material procurement, supplier coordination, and inventory management. These conditions disrupted project implementation and reduced the company's operational efficiency. Therefore, a more effective implementation of Supply Chain Management through stronger supplier coordination, more accurate material planning, and improved inventory control is necessary to enhance distribution efficiency and support the successful completion of construction projects.